Proteomic analysis for the study of amniotic fluid protein composition - Perluigi, Marzia (Journal of prenatal medicine, 2009)
Amniotic fluid (AF), routinely used for prenatal diagnosis, contains large amounts of proteins produced by the amnion epithelial cells, fetal tissues, fetal excretions and placental tissuesAlthough many amniotic fluid proteins have been identified and are currently used to detect potential fetal anomalies, little is known about the functions of these proteins and how they interact with one another. Identification of changes in the protein content of amniotic fluid, therefore, may be used to detect a particular type of pathology, or to ascertain a specific genetic disorder. In the present work we used a proteomic approach, combining 2DE and MS, in order to study the protein composition of AFS